Analisis Laju Pengeringan Gabah pada Mesin Pengering Gabah Tipe Flat Bed Dryer di Kampung Salor Indah Distrik Kurik Kabupaten Merauke - Bambang Irawan; Mega Ayu Yusuf; Parjono Parjono (Musamus AE Featuring Journal, 2023)
Grain drying machines have been widely used by farmers throughout the archipelago, including in Merauke because of their practical and easy-to-use advantages. The purpose of this study was to determine the drying rate of grain drying machines. Grain drying machine is one of the solutions in dealing with post-harvest rice problems faced by farmers when the rainy season comes. Drying machines have several drawbacks, including in determining the drying rate and grain moisture content which cannot be ascertained, which affects grain quality. Based on the facts in the field so far the owners of grain drying machines do not yet have instruments for measuring moisture content and temperature in the drying machines, determining the drying rate is only based on estimates by biting or breaking. From the research results, it was found that the optimal temperature range in the drying process of the flat bed dryer type was 29 oC – 31oC, the optimal drying time was at 35 hours with the grain moisture content obtained being 14%.